Crack growth in glass matrix composite reinforced by long SiC fibres - Kotoul, Michal; Vyslouzil, Tomas; Boccaccini, Aldo R.; Dlouhy, Ivo (Theoretical and Applied Fracture Mechanics, 2008)
Theoretical and experimental work are made for bridged cracks in chevron-notched three point bend specimens made of glass matrix composite reinforced by long SiC fibres. The fracture toughness (KIC) values are determined using the chevron-notch technique and compared with the theoretical predictions based on micromechanical analysis exploiting weight functions. The weight functions for orthotropic material are obtained numerically by means of detailed FEM analysis using the ANSYS package and they are further used together with appropriate bridging models for the theoretical prediction of the R-curve behaviours typical of the investigated composites. © 2007 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.crackg
Keywords: Brittle matrix composites; Chevron-notch specimen; Crack bridging; R-curve modelling; SiC fibres; Weight functions